Evaluation of ultrasonic, acid, thermo-alkaline and enzymatic pre-treatments on anaerobic digestion of Ulva rigida for biogas production. (July 2015) - Karray, Raida; Hamza, Manel; Sayadi, Sami
Highlights: Green macroalga Ulva rigida was used as feedstock for biogas production. Four pre-treatment of U. rigida were used to enhance biogas production. After enzymatic hydrolysis of U. rigida reducing sugar reached 7.3 g/L. The best biogas yield 626.5 mL/g CODint was obtained after enzymatic hydrolysis. Abstract: Pre-treatment of macroalgae has received considerable research globally due to its influence on the technical, economic and environmental sustainability of algae biogas production. Some of the most promising pre-treatment methods require the application of chemicals, enzymatic, and mechanical. This study focused on these pre-treatments of Ulva rigida for biogas production. The evaluation of different pre-treatment in terms of reducing sugar yields demonstrates that 3.62, 2.88, 2.53 and 7.3 g/L of reducing sugar was obtained in acid catalysis, thermoalkaline, ultrasonication and enzymatic pre-treatment, respectively. However in crude macroalgae only 0.6 g/L of reducing sugar was given. After anaerobic digestion, the enzymatic hydrolysis was demonstrated the best biogas yield than other pre-treatment which reached 626.5 mL/g CODint with 62.65% of biodegradability. The best demonstrated method which uses crude broth of Aspergillus niger showed an effective and environmentally friendly strategy for enhancing the biogas production yields after the anaerobic digestion.